2010
DOI: 10.1002/anie.201002087
|View full text |Cite
|
Sign up to set email alerts
|

Salen‐Complex‐Mediated Formation of Cyclic Carbonates by Cycloaddition of CO2 to Epoxides

Abstract: Metal complexes of salen ligands are an important class of compounds, and they have been widely studied in the past. Among their successful catalytic applications, the synthesis of cyclic carbonates by the coupling reaction of epoxides with CO(2) has received increased attention; this is mostly due to the importance of using a greenhouse gas as a feedstock for the synthesis of useful molecules. Herein the most relevant past and present research surrounding this topic is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
318
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 770 publications
(322 citation statements)
references
References 84 publications
0
318
0
4
Order By: Relevance
“…Therefore, the nucleophile can be embedded or weakly coordinated to the catalyst resulting a in a dual effect: it can act as a nucleophile in the ring-opening of the epoxide and/or favor the coordination of the oxirane to the metal center by a trans ligand effect. 13 Salen and salphen catalysts are characterized by an easy preparation, allowing for large-scale synthesis and potential commercial applications. They can also be fine-tuned from a reactivity point of view, by ad hoc structure modifications; the possibility of direct inclusion of a nucleophilic co-catalyst, variation in the type of active metal center, and formation of mono-and multinuclear catalysts.…”
Section: Development Of Improved Reactivity In Coc Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the nucleophile can be embedded or weakly coordinated to the catalyst resulting a in a dual effect: it can act as a nucleophile in the ring-opening of the epoxide and/or favor the coordination of the oxirane to the metal center by a trans ligand effect. 13 Salen and salphen catalysts are characterized by an easy preparation, allowing for large-scale synthesis and potential commercial applications. They can also be fine-tuned from a reactivity point of view, by ad hoc structure modifications; the possibility of direct inclusion of a nucleophilic co-catalyst, variation in the type of active metal center, and formation of mono-and multinuclear catalysts.…”
Section: Development Of Improved Reactivity In Coc Synthesismentioning
confidence: 99%
“…1,2,6 Despite the disadvantage of CO 2 having sluggish reactivity, recent work has unambiguously demonstrated that new opportunities may become available when proper catalytic methods are designed that help to improve the reactivity, selectivity and/or sustainability profiles of such processes. Among the most widely studied reactions in CO 2 catalysis is the formation of cyclic organic carbonates (COCs) [11][12][13][14][15][16][17][18] apart from their analogous and related linear carbonates 19 and poly(carbonates). [20][21][22] These COCs have been frequently associated with numerous applications involving them as non-protic solvents, precursors for poly(carbonate) synthesis, electrolyte solvents and more recently as useful intermediates in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[142][143][144][145] One of the most successful classes of catalysts are cobalt, chromium and aluminium salen complexes, which have also allowed the development of asymmetric variations of the reaction. [146] The reaction with cumulenes is not limited to CO2. In particular, isocyanates, isothiocyanates and carbodiimides react with epoxides to give the corresponding five-membered heterocycles.…”
Section: Formal [3+2] Cycloadditions With Cumulenesmentioning
confidence: 99%
“…Therefore, chemical fixation of CO2 has been a hot topic from the viewpoint of sustainable development and green chemistry. In this regard, one of the most promising strategies is the transformation of CO2 with epoxides to yield the corresponding cyclic carbonates (Scheme 1) [3], which is considered green because of 100% atom efficiency. Also cyclic carbonates can be widely applied in proton inert solvents, as precursors for polycarbonates and polyurethanes synthesis, as electrolytes in lithium secondary batteries, and as intermediates for production of pharmaceuticals, fine chemicals and agricultural chemicals [4,5].…”
Section: Introductionmentioning
confidence: 99%